Efeito do manejo da vegetação espontânea em cafezal sobre ácaros da mesofauna edáfica - Marafeli, Patrícia de Pádua (2016)
The study not only of micro arthropods of edaphic community, but also of litter is very important, because we know that it is the portion of the ground where are found large quantities of specimens, when compared with the ground without the layer of leaf litter, for this portion to provide adequate habitat for a large number of beneficial micro arthropods. The objective of this study was to evaluate the effect of methods of spontaneous vegetation management in coffee plantation on the richness, abundance, dominance, diversity and equitability of mites of the edaphic mesofauna and the effect of seasonality on this community. The soil samples were carried out between the lines of coffee plantation, with different methods of management of spontaneous vegetation, such as residual herbicide, without weeding, manual weeding, agricultural grid, contact herbicide, rotary machine, agricultural mower and in an environment of forest. For the soil samples was used a probe cylindrical steel for intact soil samples and the extraction of mites was performed in laboratory by means of the Berlese-Tullgren funnel. Comparisons of the mites community in the different types of management of weeds were made by using ecological indexes. From the data obtained were calculated the faunal wealth, diversity and uniformity across the indices of Shannon (h) and Pielou (e) and the similarity between the species in the different systems (Bray-Curtis) by using the Past software. It was also performed the faunistic analysis using the ANAFAU test. Soil samples were made in coffee plantation in the Experimental Field of EPAMIG, in São Sebastião do Paraíso, MG, during the years 2013 and 2014, in dry and rainy seasons of each year, and the extraction of mites of the mesofauna was done at the Laboratory of Acarology of EPAMIG Sul/EcoCentro, in Lavras, as well as other activities related to the study. In general, the management of spontaneous vegetation has affected the community of edaphic mites, especially the use of residual herbicide, which negatively affected. There was a difference in the communities of mites between treatments in the two periods studied, being the dry season more favorable to the mites that the rainy season. Oribatid mites were dominant in the two years and in both periods studied. There was difference in the richness, diversity, abundance and equitability of edaphic mites according to the management of the spontaneous vegetation. The environment without management of the spontaneous vegetation, such as native forest presented greater richness and diversity in relation to environments with vegetation management.